2021
DOI: 10.1111/jop.13154
|View full text |Cite
|
Sign up to set email alerts
|

Signaling alterations in oral keratinocytes in response to shisha and crude tobacco extract

Abstract: Background: Tobacco consumption in smoking and non-smoking forms has been consequential in the rise of oral cancer cases. Among different forms, epidemiological studies from Middle Eastern countries and rural parts of northern India have reported increasing association of oral cancer with waterpipe (hookah) smoking. However, molecular mechanisms and role played by waterpipe smoking in the onset of oral carcinogenesis remains unexplored. Methods: In this study, immortalized normal human oral keratinocytes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Two exclusive microbiological studies were removed 27,28 , same to animal studies 29,30 . One study was not found 31 . Manual search has retrieved no additional paper.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Two exclusive microbiological studies were removed 27,28 , same to animal studies 29,30 . One study was not found 31 . Manual search has retrieved no additional paper.…”
Section: Resultsmentioning
confidence: 97%
“…Three studies were in vitro 4,32,33 , and biological samples were obtained from patients in 17 studies 8,31,[33][34][35][36][37][39][40][41][42][43][44][45][46][47][48] . In addition, the levels of pro-inflammatory cytokines, the receptor activator of nuclear factor-κB (RANKL), and osteoprotegerin were evaluated [34][35][36] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation